Sistema web para la gestión de información del Departamento de Seguimiento de Graduados de la Universidad Técnica de Cotopaxi Extensión La Maná. - Pilaguano Ayala, Rubén Orlando (2020)
The research project proposed as web system for information management of the department of graduate monitoring of the Technical University of Cotopaxi extension La Mana, was developed with tools such as MySQL, PHP, phpMyAdmin, Apache, laravel, JavaScript and Bootstrap. The web system has been developed considering the requirements that were manifested by those who will use this project, through the constant dialogue and revision followed by the advances of the web system and thus to obtain a software free of errors, the requirements that were used are Control of access to users, register information of graduates, consult data of one or all graduates, search for graduates by ID or by career, edit data of graduates stored in the system, manage user accounts with access to the system, add digital project of the graduates, generate a report of the graduates registered in the system, generate a pdf of the complete information of the graduates, generate a statistical graph of the number of graduates by career, register faculties and careers of the UTC, delete faculties and careers and modify data of faculties and careers. The security within the system is a very important point since by the very fact of being in the network it runs the risk of being manipulated. Therefore, the system will have a screen specially designed for user authentication, that is, a login, allowing only authorized people to enter the system, helping to keep the data and the system safe.